Analysis of biochemical changes in cultivars of Black gram, Green gram and Pea against powdery mildew - Waghmare, P P; Nasreen, Sahera (Plantae Scientia, 2019)
Powdery mildew disease of the Black gram, Mung bean and Pea are a major constraint in the production. The resistance of plants to various pathogens depends on synthesis and level of various defence enzymes like hydrolases; peroxidases and antimicrobial compounds like phytoalexins (Kuc, l991 et al Kauffmann et al. l987; Boiler, l987; Mauch et al., l988; Kale and Choudhary 200l, Koche and Choudhary, 2005). The present study focused on visual screening of selected crop cultivars against the powdery mildew and its biochemical correlation with chlorophyll content, sugars, phenols content, PR-proteins and Phytoalexin activities. From the field studies, it was observed that selected crop was found with powdery mildew incidence. This disease incidence data was correlated with biochemical changes and level of chlorophyll, sugars, phenols, PR-protein and Phytoalexin activities.